Identifikasi Penerapan Arsitektur Tradisional Jawa Studi Kasus Pendhapa Pura Mangkunegaran Surakarta - Yusron, Ridwan Arbai; Raidi, Samsudin (Prosiding (SIAR) Seminar Ilmiah Arsitektur, 2020)
Javanese traditional architecture or custom building is one of the national assets that has extraordinary special meaning and needs to be preserved. Traditional architecture from various ethnic groups in Indonesia has been studied and documented. As for those who have not been studied, Javanese traditional architecture actually has certain characteristics and uniqueness that can be used as basic capital in tourism development. Specifically operational management and how it plays a role in the building under study. the purpose of this research is to recommend to the community and to find out the extent to which the concept is applied to cultural-specific buildings, as well as the role and impact of communities living around the building area. This research was conducted in one of the cultural buildings in downtown Surakarta, namely Pura Mangkunegaran. This research uses a descriptive analytic approach which is a method that serves to describe or give an overview of the object under study or data as it is without analyzing. Then make conclusions that apply to the public with qualitative data. Data collection methods use observation, interviews, and in-depth discussion of literature studies. The application of the above method is accompanied by guidelines regarding the history of the establishment of the Pura Mangkunegaran because this research was focused on buildings. The expected results of these research data is the concept of traditional Javanese architecture that has been applied to the building can be an evaluation material for related parties and can be used as a reference to improve the quality of the building.